Novel Chromosome-Borne Accessory Genetic Elements Carrying Multiple Antibiotic Resistance Genes in Pseudomonas aeruginosa - Yu, Ting; Yang, Huiying; Li, Jun; Chen, Fangzhou; Hu, Lingfei; Jing, Ying; Luo, Xinhua; Yin, Zhe; Zou, Mingxiang; Zhou, Dongsheng (Frontiers in Cellular and Infection Microbiology, 2021)
Pseudomonas aeruginosa is noted for its intrinsic antibiotic resistance and capacity of acquiring additional resistance genes. In this study, the genomes of nine clinical P. aeruginosa isolates were fully sequenced. An extensive genetic comparison was applied to 18 P. aeruginosa accessory genetic elements (AGEs; 13 of them were sequenced in this study and located within P. aeruginosa chromosomes) that were divided into four groups: five related integrative and conjugative elements (ICEs), four related integrative and mobilizable elements (IMEs), five related unit transposons, and two related IMEs and their two derivatives. At least 45 resistance genes, involved in resistance to 10 different categories of antibiotics and heavy metals, were identified from these 18 AGEs. A total of 10 β-lactamase genes were identified from 10 AGEs sequenced herein, and nine of them were captured within class 1 integrons, which were further integrated into ICEs and IMEs with intercellular mobility, and also unit transposons with intracellular mobility. Through this study, we identified for the first time 20 novel MGEs, including four ICEs Tn6584, Tn6585, Tn6586, and Tn6587; three IMEs Tn6853, Tn6854, and Tn6878; five unit transposons Tn6846, Tn6847, Tn6848, Tn6849, and Tn6883; and eight integrons In1795, In1778, In1820, In1784, In1775, In1774, In1789, and In1799. This was also the first report of two resistance gene variants blaCARB-53 and catB3s, and a novel ST3405 isolate of P. aeruginosa. The data presented here denoted that complex transposition and homologous recombination promoted the assembly and integration of AGEs with mosaic structures into P. aeruginosa chromosomes.